Introducing SEC–SANS for studies of complex self‐organized biological systems. Issue 12 (3rd January 2019) - Johansen, Nicolai Tidemand; Pedersen, Martin Cramer; Porcar, Lionel; Martel, Anne; Arleth, Lise
Abstract : Small‐angle neutron scattering (SANS) is coupled with online size‐exclusion chromatography (SEC). The obtained SEC–SANS was combined with SEC–SAXS and utilized to investigate solution structures of phospholipid nanodiscs with and without incorporated membrane proteins. Abstract : Small‐angle neutron scattering (SANS) is maturing as a method for studying complex biological structures. Owing to the intrinsic ability of the technique to discern between 1 H‐ and 2 H‐labelled particles, it is especially useful for contrast‐variation studies of biological systems containing multiple components. SANS is complementary to small‐angle X‐ray scattering (SAXS), in which similar contrast variation is not easily performed but in which data with superior counting statistics are more easily obtained. Obtaining small‐angle scattering (SAS) data on monodisperse complex biological structures is often challenging owing to sample degradation and/or aggregation. This problem is enhanced in the D2 O‐based buffers that are typically used in SANS. In SAXS, such problems are solved using an online size‐exclusion chromatography (SEC) setup. In the present work, the feasibility of SEC–SANS was investigated using a series of complex and difficult samples of membrane proteins embedded in nanodisc particles that consist of both phospholipid and protein components. It is demonstrated that SEC–SANS provides data of sufficient signal‐to‐noise ratio for these systems, while at the same time circumventing aggregation. By combining SEC–SANS and SEC–SAXS data, an optimized basis for refining structural models of the investigated structures is obtained.